Redescriptions of Armigeres annulipalpis and Armigeres flavus (Diptera: Culicidae) from Sarawak, Malaysia - Toma, T.; Miyagi, I.; Okazawa, T.; Higa, Y.; Wong, S.F.; Leh, M.U.; Yong, Hoi Sen (Akademi Sains Malaysia & Confederation of Scientific & Technological Association in Malaysia (COSTAM), 2012)
Redescriptions and illustrations of the pupae and larvae of Armigeres (Leicesteria) annulipalpis (Theobald) and Ar. (Lei.) flavus (Leicester) were made based on the specimens collected in Sarawak, Malaysia. Illustrations of abdominal ornamentation of adults and male genitalia were also given. The larvae of Ar. annulipalpis were found mainly in water accumulation of green bamboo stumps and splits. Armigeres flavus was commonly found in bamboo stumps and containers with very turbid water in mountain forests.